1994
DOI: 10.1007/bf00863771
|View full text |Cite
|
Sign up to set email alerts
|

Changes in peripheral blood lymphocyte subset frequencies in myasthenia gravis patients are related to immunosuppression

Abstract: Surface antigens on peripheral blood lymphocytes from myasthenia gravis patients were investigated. The expression of DR+ and CD8+/DR+ T lymphocytes was increased and the expression of CD4+ T cells reduced. Neither thymectomy, clinical condition nor anti-acetylcholine receptor antibody titre correlated with any of the changes in peripheral blood lymphocyte subsets observed. However, immunosuppressive therapy correlated with the significant reduction in CD4+ and CD2+/CD4+ T cells in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…These results also suggested that there was no difference in CD4 + cell activation in relation to Pglycoprotein activity between thymectomized and unthymectomized MG patients. Crosti et al have observed that the frequency of CD4 + T cells was significantly reduced in immunosuppressed MG patients who were treated with GC alone or associated with azathioprine compared with non-immunosuppressed patients and a healthy control, but the frequency of CD8 + T cells was not significantly changed [5].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These results also suggested that there was no difference in CD4 + cell activation in relation to Pglycoprotein activity between thymectomized and unthymectomized MG patients. Crosti et al have observed that the frequency of CD4 + T cells was significantly reduced in immunosuppressed MG patients who were treated with GC alone or associated with azathioprine compared with non-immunosuppressed patients and a healthy control, but the frequency of CD8 + T cells was not significantly changed [5].…”
Section: Discussionmentioning
confidence: 93%
“…CD8 + T cells have also been reported to be involved in the induction and persistence of experimental autoimmune MG (EAMG) by directly or indirectly affecting AChR-reactive T cells and anti-AChR IgG antibody-secreting cells [4]. On the other hand, the influence of immunosuppressive therapy and thymectomy on peripheral-blood lymphocyte subset frequencies has been reported [5].…”
Section: Introductionmentioning
confidence: 98%
“…Our data also showed the same alteration of the lymphocyte subsets with increasing erythropoietin levels. However, such an alteration of the lymphocyte subset was also observed in MG patients [15]. Masuda demonstrated an increase in blood CD8 + cells and a monoclonal rearrangement of the T-cell receptor h chain gene both in the peripheral blood and the thymoma.…”
Section: Discussionmentioning
confidence: 94%
“…While the steroid effect appears rapidly, the clinical effect of other immunosuppressants may take a few weeks and up to several months to develop. Immunosuppressive drugs act at many levels of the immune system, inhibiting both cellular and humoral mechanisms and reducing the damage caused by autoimmunity in MG. Immunosuppressive therapy, but no other therapy in MG and not thymectomy, causes significant reduction in CD4 + and CD2 + /CD4 + T cells in the peripheral blood (79). These drugs can be associated with several serious side effects, and the treatment should be monitored carefully (80, 81).…”
Section: Pharmacological Treatmentmentioning
confidence: 99%